Management of diabetic retinopathy - Saxena Sandeep (Indian Journal of Ophthalmology, 2000)
Diabetic retinopathy remains a major cause of blindness despite increased understanding of this disease and identification of successful treatments. The Diabetic Retinopathy Study identified risk factors associated with a high risk of blindness and confirmed the benefits of panretinal photocoagulation. The Early Treatment Diabetic Retinopathy Study defined the retinal characteristics, indications of treatment and results of laser treatment of clinically significant macular oedema. The Diabetic Retinopathy Vitrectomy study established the benefits and timing of vitrectomy for non-clearing vitreous haemorrhage and severe proliferative diabetic retinopathy. The Diabetes Control and Complications Trial and the United Kingdom Prospective Diabetes Study have also demonstrated the value of tight control of blood sugar and blood pressure in diabetic retinopathy. These studies developed specific recommendations for the management of diabetic retinopathy. Optimum use of this information can minimize visual loss due to diabetic retinopathy.